UPAYA HUKUM PENGESAHAN PERKAWINAN BAGI PERKAWINAN YANG TIDAK DICATATKAN DITINJAU DARI UU NO. 1 TAHUN 1974 DAN KOMPILASI HUKUM ISLAM (KHI) - Eko Gani PG; Hasballah Thaib; Hasim Purba; Idha Aprilyana Sembiring (Universitas Sumatera Utara, 2018)
ABSTRACT Basically the marriage is the emotional and physical bond between a man and woman as husband and wife with the aim of forming a family (household) happy and everlasting based on the Supreme Godhead as stated in Act 1 of 1974 about the marriage Article 1 The marriage is the way advocated by Religion, Law and Culture in order to keep individualis away from bad things such as adultery, sexual deviation, and others. Marriage is lawful if done according to the religious law of each article 2 paragraph 1 of Act No. 1 Year 1974 and in paragraph 2 mentioning each marriage is registered according to the prevailing laws and regulations. However, in fact the marriage are also not registered, resulting in the loss of rights of the parties to the marriage. Based on the research results could be concluded that are several factors that affect the marriages are unregistered, both economic factors where marriage took place. Furthermore, the unregistered marriage also gives legal effect to the parties, according to Act No. 1 of 1974 article 2, paragraph 1, that marriages which are carried out according to their respective religious law are considered valid but according to Act No. 1 of 1974 article 2 paragraph 2 dose not fulfil the administration as determined by legislations. And the legal efforts that can be taken by the parties who did the unregistered marriage by way of proposing the marriage Itsbat and marriage Keywords : Itbat, The Legal Efforts, Endorsement, The Unregistered Marriage.